The influence of income inequalities on socio-economic development in the European Union - Litwiński, Michał (Wpływ nierówności dochodowych na rozwój społeczno-ekonomiczny w Unii Europejskiej, 2019)
Recently, there has been observed intensified research on the impact of income inequalities on aspects of socio-economic development in the European Union. However, there are no comprehensive analyses concerning the relationship between these phenomena. Therefore the subject of the paper is the influence of income inequalities on socio-economic development. The author would like to verify the hypothesis that the character of the impact of income inequalities on socioeconomic development in the European Union is negative. Analysis was conducted for the European Union in 2004-2017 using the panel data model, also estimated was the synthetic indicator of socioeconomic development. The research conducted in the paper leads to ambiguous conclusions. On the one hand, inequalities measured for the whole distribution of income have no influence on socioeconomic development in the European Union. However, the income gap between the richest and the poorest hinders the mentioned phenomenon.
Econometrics = Ekonometria, 2019, Vol. 23, No. 1, s. 45-60
Keywords: income inequalities; socio-economic development; economic growth; panel model; Gini coefficient; S80/S20 ratio; nierówności dochodowe; rozwój społeczno-ekonomiczny; wzrost ekonomiczny; model panelowy; współczynnik Giniego; wskaźnik S80/S20